Formação continuada de professores e avaliação externa: os sentidos atribuídos pelos professores de Língua Portuguesa - Carvalho, Ana Carolina Medeiros Gatto Vieira (2016)
This present paper, initiated in 2013, aims to investigate which meanings are attributed by Portuguese teachers at the State Public Network in a city of São Paulo on the main actions of Continuing Education offered by the Ministry of Education in the period of 2009 -2014 in the context of Educational Achievement Assessment System of São Paulo State (SARESPPortuguese initials). The survey data have three sources: documents concerning the SARESP and continuing education programs of the Department of Education of the State of São Paulo, the questionnaire and the interviews of the selected teachers to search. It is worth mentioning the involvement of the researcher in this process, since she is involved in the training of teachers as a Professor Coordinator of the Pedagogical Center with the Educational Board, a relationship which enabled the construction of the research unrest. The main theoretical frameworks for the discussion of the theme of the project are: VYGOTSKY (2000) for a discussion of "sense and meaning" BALL (2001,2004, 2005), for analysis of "global policy guidelines," AFONSO (2009), FREITAS (2011, 2012, 2014) and LUCKESI (2006, 2008, 2011) for discussions on assessment, GATTI (2008, 2009), NÓVOA (1992) and PEREZ GOMES (1992) for teacher training, ANDRÉ and LÜDKE (2013) for qualitative research approach in education. From the analysis of the collected data can be inferred that the relationship between external evaluation and teacher training has progressively undermined these actions over the years, primarily by emphasizing the subjects charged at SARESP and prioritize the issues that make up the evidence. Regarding the meanings attributed by the teachers you can see that they recognize the teacher accountability processes as a result of external evaluation of policies; They realize the importance of continuing education and the influence of external assessments of such training and asked that the formations consider their experiences, their practice and the context in which they develop their activities.